An investigation on morphology of hard-brittle silicon surface by diamond grinding - Konneh, Mohamed; Izman, S.; Ali, Mohammad Yeakub (2006)
Silicon like any hard and brittle material is well known for its low machinability unless it is machined under ductile mode condition. Selection of appropriate machining parameters would result in production of fine streaks on the machined work-piece surface. Such a precision machining technique is beneficial to wafer labs and chip-making industries as surface streaks are essential for reducing polishing time. This paper deals with an experimental investigation on surface quality in terms of the morphology of ground silicon surface (i.e. ductile streaks generated on silicon during partial-ductile mode diamond grinding). The process factors involve the machining conditions such as speed, feed rate and depth of cut. A specially modified machine tool that has an air driven low powered high-speed attachment was used for the machining. Results indicate that partial-ductile streaks as well as some fractures and pits are formed on the ground silicon surfaces.